Exploring health and toxicity in food choices: 10 examples navigating the gray area - Bast, Aalt; Semen, Khrystyna O. (Frontiers in Nutrition, 2024)
People's perception on what is healthy and what is toxic food, determines food preferences and eating behavior. The difference between heathy and toxic food and food ingredients is however not always clear. This is illustrated with ten examples. Unjustly, all-natural food is regarded as safe. Regulation on health claims on food and food risks is not balanced. Biphasic responses of the physiological effect of food ingredients show that mild toxicity of these substances results in health promotion. Nutritional substances with drugs may have either a negative or a positive effect on health. New toxicological methodologies can be brought into play, to better understand the dynamics of health and disease. Unfortunately, we still cannot taste toxicity.